Serial [18F]-fluoromisonidazole PET during radiochemotherapy for locally advanced head and neck cancer and its correlation with outcome. Issue 1 (October 2015) - Wiedenmann, Nicole E.; Bucher, Sabine; Hentschel, Michael; Mix, Michael; Vach, Werner; Bittner, Martin-Immanuel; Nestle, Ursula; Pfeiffer, Jens; Weber, Wolfgang A.; Grosu, Anca L.
Abstract Purpose The aim was to assess changes of tumour hypoxia during primary radiochemotherapy (RCT) for head and neck cancer (HNC) and to evaluate their relationship with treatment outcome. Material and methods Hypoxia was assessed by FMISO-PET in weeks 0, 2 and 5 of RCT. The tumour volume (TV) was determined using FDG-PET/MRI/CT co-registered images. The level of hypoxia was quantified on FMISO-PET as TBRmax (SUVmaxTV/SUVmean background). The hypoxic subvolume (HSV) was defined as TV that showed FMISO uptake ⩾1.4 times blood pool activity. Results Sixteen consecutive patients (T3–4, N+, M0) were included (mean follow-up 31, median 44 months). Mean TBRmax decreased significantly (p < 0.05) from 1.94 to 1.57 (week 2) and 1.27 (week 5). Mean HSV in week 2 and week 5 (HSV2 = 5.8 ml, HSV3 = 0.3 ml) were significantly (p < 0.05) smaller than at baseline (HSV1 = 15.8 ml). Kaplan–Meier plots of local recurrence free survival stratified at the median TBRmax showed superior local control for less hypoxic tumours, the difference being significant at baseline and after 2 weeks (p = 0.031, p = 0.016). Conclusions FMISO-PET documented that in most HNC reoxygenation starts early during RCT and is correlated with better outcome.